ELECTROCHEMICAL BEHAVIOR OF ZINC ANODE IN ACIDIC ZINC ELECTROLYTE - INFLUENCE OF LEAD AS AN IMPURITY IN ZINC ANODIC DISSOLUTION - Kherrab-Boukezzata, Habiba; Ghemmit-Doulache, Naima; Bounoughaz, Moussa; Boutarfaia, Slimane (Journal of Fundamental and Applied Sciences, 2022)
Zinc is common metal used for steel protection. In this work, an alloy Zn-1 % wt. Pb was prepared by fusion at 500°C. The analysis of the corrosion behavior was studied with pure Zn anode as control in aerated solution of 0.9 M ZnSO4.7H2O + 1.63 M H2SO4 at 38°C.The effect of lead impurity on corrosion resistance of zinc anode in zinc electrorefining process was investigated using open circuit potential (OCP), Tafel plots, chronoamperometry at imposed constant anodic potential and electrochemical impedance spectroscopy (EIS) techniques. Samples were characterized by chemical analysis, optic microscope (OM) and X-ray diffraction (XRD). The results show that the lead impurity leads to degradation of the behavior of the alloy due to negative effect on the microstructure. Lead increases the corrosion rate and decreases the corrosion resistance of Zn-1 % wt. Pb alloy.